Public Service Bureaucratic Reform: A Case Study on Coordination in One Stop Services (KPTSP) in Takalar Regency - Gita Susanti; Rifany Rifany (Publik : (Jurnal Ilmu Administrasi), 2020)
Bureaucratic services tend not to improve their performance and carry out reforms. Service users are often faced with so many problems when they are dealing with bureaucracy. The purpose of this study is to describe the reform of the Public Service Bureaucracy in terms of coordination in One Stop Services (KPTSP) in Takalar Regency. In this study, a qualitative approach was used. The type of research used in this research is descriptive research type. The results showed that hierarchical mechanisms in the form of a structured flow of coordination and power need each other to establish cooperation within organizational units. The market mechanism shows that the change in the bureaucracy from services to revenue to provide income for the region through the collection of fees. Licensing and providing incentives can improve the performance of One-Stop Services, Takalar District has a network mechanism that is interrelated and needs each other, this can be seen from the requirements given by the Service Agency One-Stop Integrated Takalar Regency that asks for recommendations from related Regional Work Units (SKPD).